Tidlige skoleforbindelser: Svensk-norsk ideutveksling på skolens område rundt midten av det 19. århundre og dannelsen av tekstkulturer over kjølen - Roos, Merethe (Nordic Journal of Educational History, 2018)
Early School Connections: Swedish-Norwegian Exchange of Ideas and the Formation of Textual Cultures Across the Border in the Mid-Nineteenth Century When it comes to the development of school and education between 1814 and 1905, the relation between Norway and Sweden has only been superficially subject to previous research, even though sources can verify contact and transfer of ideas already as early as in the beginning of the 1850’s. In this article, I will argue that Norway and Sweden are connected in common textual cultures, which gives a distinctive direction for the development of the school in the following decades. A textual culture refers to the material processes and ideological formations surrounding the production, transmission, reception, and regulation of texts. It studies the interaction between these processes and formations in order to show how texts get made and how they are understood. The textual cultures will here be studied on the background of Hartvig Nissen’s articles in the newspaper Morgenbladet in 1855, as well as a discussion between the school periodicals Almueskoletidende og Den Norske Folkeskole in 1861.